Risk Factors for Dieulafoy Lesions in the Upper Gastrointestinal Tract - Shin, Hae Jin; Ju, Jong Seok; Kim, Ki Dae; Kim, Seok Won; Kang, Sung Hoon; Kang, Sun Hyung; Moon, Hee Seok; Sung, Jae Kyu; Jeong, Hyun Yong (Clinical endoscopy, 2015)
The purpose of this study is to verify the risk factors associated with Dieulafoy lesion formation in the upper gastrointestinal tract. A case-control study was performed by reviewing the electronic medical records of 42 patients who were admitted to a tertiary medical center in the Daejeon region for Dieulafoy lesions from September 2008 to October 2013, and the records of 132 patients who were admitted during the same period and who underwent endoscopic examination for reasons other than bleeding. We analyzed clinical and endoscopic findings retrospectively, and searched for risk factors associated with Dieulafoy lesion formation. All 42 patients diagnosed with Dieulafoy lesion had accompanying bleeding, and the location of the bleeding was proximal in 25 patients (59.5%), the middle portion in seven patients (16.7%), and distal in 10 patients (23.8%). Antiplatelet agents (p=0.022) and alcohol (p=0.001) use showed statistically significant differences between the two groups. The odds ratios (95% confidence intervals) of the two factors were 2.802 (1.263 to 6.217) and 3.938 (1.629 to 9.521), respectively. This study showed that antiplatelet agents and alcohol consumption were risk factors associated with Dieulafoy lesion formation in the upper gastrointestinal tract.